The bindingness of mazhab in Islamic banking contracts in Malaysia - Muhammad Azri, Mohd Akhir (2018)
An issue of differing views among scholars from various mazhab on any unresolved fiqh issue poses confusion in the public. It also happens in dealing with Islamic banking contracts. There is a need for the final word that determines the right view of mazhab, especially for the law institutions which aimed at providing solutions to problems. Researchers have conducted an analysis on legal materials regulating Islamic banking institutions in Malaysia to see how this problem is addressed. This study has two objectives, namely: to study the position of reference to mazhab under Malaysia legislations governing Islamic banking in Malaysia and to study the application of reference to mazhab in Shariah Resolution of Shariah Advisory Council (SAC) of Bank Negara Malaysia (BNM) pertaining to Islamic Banking contract. The researcher found general provision in legislation regulating Islamic banking institutions in Malaysia on the prevailing practices of mazhab. The power to interpret the Islamic law lies with the Shariah Advisory Council. The researcher also conducted an analysis on Shariah Resolutions, founded that Shariah Advisory Council in determining the necessity of a contract has followed the fundamental basis of the proposal Usul al-Fiqh by referring to the Holy Quran and Sunnah, ijmak, and then referring to the view of the scholar of the mazhab. The Shariah Advisory Council has opennes by examining all the views of the four mazhab muktabar. It is found that there is no tendency to prioritize any mazhab as opposed to other mazhab because there is no difference in the views between scholars of mazhab in banking contracts analyzed by the author. In conclusion, the law regulating Islamic banking is general and can be challenged by in court. However, the ultimate authority are given to the Shariah Advisory Council to control this problem from becoming more critical.